High-accuracy mass spectrometry based screening method for the discovery of cysteine containing peptides in animal venoms and toxins - Oosten, Luuk N. van; Pinkse, Martijn W. H.; Pieterse, Mervin; Escoubas, Pierre; Verhaert, Peter D. E. M. (Peptidomics, 2018)
Venom and toxin samples derived from animal origins are a rich source of bioactive peptides. A high proportion of bioactive peptides that have been identified in venom contain one or more disulfide bridges, which are thought to stabilize tertiary structure, and therefore influence the peptides' specificity and activity. In this chapter, we describe a label-free mass spectrometry-based screening workflow specifically to detect peptides that contain inter- and intramolecular disulfide bonds, followed by elucidation of their primary structure. This method is based on the determination of the normalized isotope shift (NIS) and the normalized mass defect (NMD) of peptides, two parameters which are heavily influenced by the presence of sulfur in a peptide, where cysteines are the main contributing residues. Using ant defensive secretions as an example, we describe the initial fractionation of the venom on strong cation exchange followed by nanoflow HPLC and mass spectrometry. High resolution zoom scan spectra of high-abundance peptides are acquired, allowing an accurate determination of both monoisotopic and average mass, which are essential for calculation of NMD and NIS. Candidate peptides exhibiting relative low NMD and high NIS values are selected for targeted de novo sequencing. By fine-tuning the collision energy for optimal fragmentation of each selected precursor ions, the full sequence of several novel inter- and intramolecular disulfide bond containing ant defensive peptides can be established.